Analytical Techniques in Androgen Anabolic Steroids (AASs) Analysis for Antidoping and Forensic Purposes - Strano-Rossi, S.; Fiore, C.; Chiarotti, M.; Centini, F. (Mini Reviews in Medicinal Chemistry, 2011)
A survey on the main analytical challenges related to the analysis of Androgen Anabolic Steroids (AASs) is reported. AASs analysis is an issue regarding antidoping analyses as well as forensic toxicology applications. This paper reports an overview of the more recent literature regarding various aspects of sample preparation, analytical techniques and interpretation of results for AASs identification in biological samples. New analytical approaches, mainly for their application to the antidoping field, are reported. The application of AASs analysis in forensic cases is also described, taking into consideration mainly the different biological samples that can be analysed for forensic purposes. Particular attention was played on the application of hair analysis as alternative biological specimen for the determination of AASs abuse.
Keywords: AAS